Study of Supercritical CO2 Physical Property Calculation Models - Min, Luyue; Liu, Minyun; Xi, Dapeng; He, Maogang; Liu, Xiangyang; Huang, Yanping (Frontiers in Energy Research, 2022)
The supercritical CO2 (SC-CO2) thermodynamic cycle has been a promising and revolutionary technology. Related research has put higher demands on CO2 physical property calculations in terms of computational accuracy and speed. In this study, the deviations between the experimental data and predicted data calculated by several models of CO2 physical property calculation were obtained. According to the comparison results, the Span–Wagner equation of state, the Vesovic model, and the free-volume viscosity model are selected to construct a set of high-precision CO2 property calculation models. For the time-consuming problem of commonly used models, new models were developed by using the polynomial fitting and interpolation method, which improved the speed of the physical property calculation by five orders of magnitude while ensuring high accuracy. On this basis, a physical property calculation program for the SC-CO2 thermodynamic cycle could be developed, which can meet the demands of engineering applications in accuracy and calculation speed.